Chrysis subcoriacea Linsenmaier 1959 - Paukkunen, Juho; Rosa, Paolo; Soon, Villu; Johansson, Niklas; Ødegaard, Frode (Zenodo, 2014)
51. Chrysis subcoriacea Linsenmaier, 1959 Chrysis longula subcoriacea Linsenmaier 1959: 160. Holotype ♀; Finland: Kyrkslätt [= Kirkkonummi] (NMLS) (examined). Chrysis subcoriacea : Valkeila 1962: 64, Erlandsson 1971: 90, Silfverberg 1981: 61, Vikberg 1986b: 68, Söderman & Vikberg 2003: 45, Soon 2004: 24, 46, Sörensson 2008a: 80, Franzén & Norén 2009: 40, Johansson 2010: 118, Orlovskytė et al. 2010: 152, Paukkunen 2010: 538, Ivarsson 2011: 43, Larsson 2012: 12, Ranta 2012: 33, Rosa & Soon 2012, Johansson 2013a: 81, Johansson 2013b: 21, Dyntaxa 2013, Soon et al. 2014: 304, 318. Chrysis longula [part.]: Kimsey & Bohart 1991: 434. Material examined. Denmark: EJ : Virklund, 2.V.1944, 2 ♂♂; NWJ : Thy, ’Nors Øregård’, 16.VI.1953, 1 ♀ (Ardö); SJ : Stensbaek plantage, 20.VI.1949, 1♀ (Worm-Hansen). * Latvia: Ķemeri, 21.VIII.1970, 1 ♀ (V. Tumšs); Ropaži, 5.VI.1966, 1 ♀ (V. Tumšs); Zabludovka, 27.VI.1967, 1 ♀ (V. Tumšs). Norway: BØ : Øvre Eiker, Lilleby, 6.V.2012, 1 ♂; Nedre Eiker, Solbergfjell, 28.VI.2012, 1 ♂ (F. Ødegaard); ON : Nord-Fron, 30.VII–1.IX.2009 1 ♀ (F. Ødegaard). * Russian Fennoscandia (total 11 exx.): Ik : Muolaa [= Pravdino]; Rautu [= Sosnovo]; Terijoki [= Zelenogorsk]; Ka : Seiskari [= Ostrov Seskar]; Viipuri [= Vyborg]; Kol : Petrozavodsk. Distribution. Denmark, Estonia, Finland, * Latvia, Norway, Sweden, *Russian Fennoscandia.—Transpalearctic: from central and northern Europe to central Asia and Japan (Linsenmaier 1997). Linsenmaier’s (1997) record from Svalbard is based on a specimen collected from ”W. Spitzbergen, Richerche Bay” in 16th of July during A.G. Nathorst's expedition of 1898. The specimen is deposited in Linsenmaier’s collection, Luzern, and most likely it is the northernmost cuckoo wasp ever collected. However, the specimen must have been accidentally imported into the area, as no host species are known to occur on Svalbard, and it is unlikely that it could have flown there by itself. Remarks. The species has been found from all the Nordic and Baltic countries except Lithuania. It has a wide distribution and the northernmost records are from Finnish Lapland ( Obb : Rovaniemi). However, it is usually scarce and found in low numbers. In Finland it has been classified as near threatened (Paukkunen 2010). The species was reported from Denmark by Soon (2004) based on three Danish specimens in ZMUC, and by Rosa & Soon (2012) on the basis of one specimen in NMLS (see data above). Rosa & Soon (2012) also reported the species from Norway based on a Norwegian specimen in NMLS (collected from AK : Oslo Bekkelaget). Also new records are known from southern Norway (see data above). C. subcoriacea was reported from Lithuania by Orlovskytė et al. (2010) and later Rosa & Soon (2012), but this record was based on a misidentified abnormal specimen of C. longula (S. Orlovskytė in litt. ). The Latvian specimens were found in the collections of LMSZ in Riga. : Published as part of Paukkunen, Juho, Rosa, Paolo, Soon, Villu, Johansson, Niklas & Ødegaard, Frode, 2014, Faunistic review of the cuckoo wasps of Fennoscandia, Denmark and the Baltic countries (Hymenoptera: Chrysididae), pp. 1-67 in Zootaxa 3864 (1) on page 37, DOI: 10.11646/zootaxa.3864.1.1, http://zenodo.org/record/4930433 : {"references": ["Linsenmaier, W. (1959) Revision der Familie Chrysididae (Hymenoptera) mit besonderer Brucksichtigung der europaischen Spezies. Mitteilungen der Schweizerischen Entomologischen Gesellschaft, 32, 1 - 232.", "Valkeila, E. (1962) Eraiden lounaissuomalaisten luonnonhistoriallisten maakuntien (V, U, St ja EH) myrkkypistiaiset (Hymenoptera, Aculeata). Lounais-Hameen Luonto, 13, 63 - 73.", "Erlandsson, S. (1971) Catalogus Insectorum Sueciae XIX. Hymenoptera: Aculeata. Entomologisk Tidskrift, 22, 87 - 94.", "Silfverberg, H. (1981) Additions to the Finnish insect fauna during the years 1976 - 1980. Notulae Entomolgicae, 61, 45 - 61.", "Vikberg, V. (1986 b) A checklist of aculeate Hymenoptera of Finland (Hymenoptera, Apocrita Aculeata). Notulae Entomologicae, 66, 65 - 85.", "Soderman, G. & Vikberg, V. (2003 [\" 2002 \"]) Suomen myrkkypistiaisten luettelo ja levinneisyys. Sahlbergia, 7, 41 - 66.", "Soon, V. (2004) Eesti kuldherilased (Hymenoptera, Apocrita, Chrysididae). Master's thesis, University of Tartu. 81 pp. Available from: http: // dspace. utlib. ee / dspace / bitstream / handle / 10062 / 1236 / Soon. pdf; jsessionid = 6617 B 92 C 3 E 468623 BC 1 5 CAC 1 E 8 B 95 C 67? sequence = 5 (accessed 1 November 2013)", "Sorensson, M. (2008 a) Inventering av solitara bin och rodlistade insekter pa Asumfaltet och vid fd. Jarnvagsovergangen i Everod / Lyngby sommaren 2007. Kristianstad vattenrike, Vattenriket i fokus 2008: 04.", "Franzen, M. & Noren, L. (2009) Gaddsteklar pa sandmarker i Blekinge - en inventering av nio lokaler i Olofstroms, Ronneby och Solvesborgs kommuner 2007 - 2008. Lansstyrelsen Blekinge lan, rapport 2009: 16, 58 pp.", "Johansson, N. (2010) Solitara gaddsteklar (Hymenoptera: Aculeata) pa tre torrangsartade lokaler i Ovre Emadalen. Entomologisk Tidskrift, 131, 113 - 130.", "Orlovskyte, S., Budriene, A. & Budrys, E. (2010) Check-list of cuckoo-wasps (Hymenoptera: Chrysididae) of Lithuania. New and rare for Lithuania insect species, 22, 141 - 156.", "Paukkunen, J. (2010) Stinging wasps. In: Rassi, P., Hyvarinen, E., Juslen, A. & Mannerkoski, I. (Eds.), The 2010 Red List of Finnish Species. Finnish Ministry of Environment & Finnish Environment Institute, Helsinki, pp. 529 - 544.", "Ivarsson, T. (2011) Insekter vid Kungsladugardshallarna Visby 2010. Visby kommun. Available from: http: // www. gotland. se / 64257 (accessed 19 August 2014)", "Larsson, S. (2012) Insekter i sand- och grustakter i Dalarna 2010. Lansstyrelsen i Dalarnas lan, PM 2012: 08, 12 + 17 pp.", "Ranta, Y. (2012) Palkaneen kultapistiaiset (Hymenoptera, Chrysididae). Diamina, 21, 30 - 35.", "Rosa, P. & Soon, V. (2012) Fauna Europaea: Chrysididae. In: Mitroiu, M. - D. (Ed.), Fauna Europaea: Hymenoptera, version 2. 5. Available from http: // www. faunaeur. org (accessed 1 November 2013)", "Johansson, N. (2013 a) Skyddsvarda insekter i gotlandska sanddyner. Lansstyrelsen i Gotlands lan, Rapporter om natur och miljo nr. 2013: 1, 107 pp.", "Johansson, N. (2013 b) Gaddsteklar pa Stora Karlso 2012. Lansstyrelsen i Gotlands lan, Rapporter om natur och miljo nr. 2013: 2, 23 pp.", "Dyntaxa (2013) Svensk Taxonomisk Databas - Swedish Taxonomic Database (version 1.1.5059.20729). Available from: http: / / www. dyntaxa. se / (accessed 1 November 2013)", "Soon, V., Budrys, E., Orlovskyte, S., Paukkunen, J., Odegaard, F., Ljubomirov, T. & Saarma, U. (2014) Testing the validity of Northern European species in the Chrysis ignita species group (Hymenoptera: Chrysididae) with DNA Barcoding. Zootaxa, 3786 (3), 301 - 330. http: // dx. doi. org / 10.11646 / zootaxa. 3786.3.4", "Kimsey, L. S. & Bohart, R. M. (1991 [\" 1990 \"]) The Chrysidid Wasps of the World. Oxford Press, New York, 652 pp.", "Linsenmaier, W. (1997) Die Goldwespen der Schweiz. Veroffentlichungen aus dem Natur-Museum Luzern, 9, 1 - 139."]}